Ampli: A Construction Set for Paperfluidic Systems. Issue 14 (15th May 2018) - Phillips, Elizabeth A.; Young, Anna K.; Albarran, Nikolas; Butler, Jonah; Lujan, Kaira; Hamad‐Schifferli, Kimberly; Gomez‐Marquez, Jose
Abstract: The design and fabrication of reconfigurable, modular paperfluidics driven by a prefabricated reusable block library, asynchronous modular paperfluidic linear instrument‐free (Ampli) block, are reported. The blocks are inspired by the plug‐and‐play modularity of electronic breadboards that lower prototyping barriers in circuit design. The resulting biochemical breadboard is a paperfluidic construction set that can be functionalized with chemical, biological, and electrical elements. Ampli blocks can form standard paperfluidic devices without any external instrumentation. Furthermore, their modular nature enhances fluidics in ways that fixed devices cannot. The blocks' ability to start, stop, modify, and reverse reaction flows, reagents, and rates in real time is demonstrated. These enhancements allow users to increase colorimetric signals, fine tune reaction times, and counter check multiplexed diagnostics for false positives or negatives. The modular construction demonstrates that field‐ready, distributed fabrication of paper analytical systems can be standardized without requiring the "black box" of craft and technique inherent in paper‐based systems. Ampli assembly and point‐of‐care redesign extends the usability of paper analytical systems and invites user‐driven prototyping beyond the lab setting demonstrating "Design for Hack" in diagnostics. Abstract : The development of reconfigurable, modular paperfluidics based on a prefabricated reusable block library is reported. These blocks form standard paperfluidic devices and also enhance fluidics in ways fixed devices cannot. The construction set can be functionalized with chemical, biological, and electrical elements. Their assembly and point‐of‐care redesign extends a paper analytical systems' usability and user‐driven prototyping beyond the lab setting.